2018
DOI: 10.1038/s41430-018-0298-4
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal thyrotropin (TSH) screening as a tool for monitoring iodine nutrition in Armenia

Abstract: From all years and from all regions, values were consistently and uniformly below the cut point of 5 mIU/L. These results show no evidence of iodine deficiency in Armenia, and suggest that neonatal TSH may be a useful tool for monitoring iodine nutrition in Armenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
2
0
3
Order By: Relevance
“…This indicates the success of both the mandatory iodine fortification of bread and the recommendation for routine iodine supplementation in pregnancy in Australia to lower the risk of iodine deficiency. This finding is consistent with studies in Ireland (36) , Armenia (38) and Switzerland (39) that showed a declining trend in the percentage of newborn TSH > 5 mlU/l after the introduction of iodine fortification or salt iodisation. However, an exploratory analysis controlling for timing of blood sample collection, birth weight, season at birth and the underlying time trend resulted in a reversing of the effect estimate and a loss of precision.…”
Section: Discussionsupporting
confidence: 91%
“…This indicates the success of both the mandatory iodine fortification of bread and the recommendation for routine iodine supplementation in pregnancy in Australia to lower the risk of iodine deficiency. This finding is consistent with studies in Ireland (36) , Armenia (38) and Switzerland (39) that showed a declining trend in the percentage of newborn TSH > 5 mlU/l after the introduction of iodine fortification or salt iodisation. However, an exploratory analysis controlling for timing of blood sample collection, birth weight, season at birth and the underlying time trend resulted in a reversing of the effect estimate and a loss of precision.…”
Section: Discussionsupporting
confidence: 91%
“…The severity, (mild, moderate and severe) is further defined by the proportion of neonates with TSH concentrations greater than 5 mIU/L. There has been a large body of literature reporting iodine deficiency status or outcomes of iodine prophylaxis programs using nTSH results, with reference to the WHO criteria [32], and in more recent literature [33,34,35,36,37,38]. Most published reports have employed dried capillary blood spots from heel-prick as recommended.…”
Section: Methods For Measuring and Assessing Iodine Nutritionmentioning
confidence: 99%
“…Поэтому частота повышенного уровня ТТГ у новорожденных является ценным показателем йодного статуса в данной популяции. Считается, что при адекватном йодном статусе частота уровней ТТГ в крови более 5 мМЕ/л не должна превышать 3% [8]. Важным достоинством этого подхода являются низкие затраты -фактически только на статистический анализ баз данных.…”
Section: совершенствование системы мониторинга йодного статуса населенияunclassified
“…3), ни по отдельным ее регионам. Однако если частота повышения ТТГ более 5 мМЕ/л в 2012 г. была 2,86%, то при включении в анализ данных детей, у которых кровь была взята ранее 2-го или позднее 5-го дня жизни, частота возрастала до 3,23%, а при включении данных потенциально недоношенных -до 3,44% [8], что могло быть неправильно расценено как наличие йодного дефицита.…”
Section: совершенствование системы мониторинга йодного статуса населенияunclassified
See 1 more Smart Citation